Biomechanical principles of symmetrical techniques in swimming sports - A. Silva; U. Persyn; V. Colman; F. Alves (Asociación Española de Ciencias del Deporte, 2010)
In symmetrical strokes, there was an evolution to more butterfly-like undulation. Since the seventies till now, almost 1500 competitive swimmers were diagnosed and advised in the Leuven Research and Evaluation Center, based on a technique analysis and a physical screening. In addition, logbook information on their age, training history and performances was available. The relations between these data, and between these data and performance in the four swimming strokes and in different style variants per stroke, were investigated in six doctor's theses (Persyn, 1978; Daly, 1984; Van Tilborgh, 1987; Colman, 1991; Zhu, 1996 and Silva 2001). Presently, the technique of about 60 breaststroke and butterfly swimmers at international level has been digitized. Based on the data obtained from this research, and on the experience in diagnosing, a kinesiological expert system was developed. Therefore, each of the shortcomings in the diagnostic systems, specified earlier, was solved step by step in the doctoral research. Thanks to this research, from the seventies till now, there was an evolution from a predominantly qualitative to quantitative diagnosis and a series of working hypotheses related to ship and animal propulsion that he needed for diagnosing were developed. Therefore, the main purpose of this paper is to present, not only the general biomechanical model of swimming velocity, but also the already confirmed working hypotheses, in specific phases in the stroke cycle, for: (i) swimming performance (corrected for sex and age in a % score); (ii) for velocity variation of the CMbody in the cycle and; (iii) for vertical displacement of the CMbody. KEY WORDS: Swimming; Symmetrical strokes; Breaststroke; Butterfly; waving